2020
DOI: 10.31686/ijier.vol8.iss5.2312
|View full text |Cite
|
Sign up to set email alerts
|

Sample size for estimation of averages of agronomic traits in cassava seedlings

Abstract: O método de multiplicação rápida melhora o uso de material de propagação. No entanto, melhorar o gerenciamento e as técnicas experimentais é crucial para avaliar a produção e a qualidade da planta. Este estudo calculou o tamanho da amostra para estimar médias de caracteres agronômicos em mudas de mandioca originárias de estacas de caule com um número diferente de folhas e diâmetros diferentes. Um total de 600 mudas (cada uma com duas gemas) com um diâmetro de 15,00 a 19,99 mm (N = 300) ou 20,00 a 25,00 mm (N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
2
2
0
4
Order By: Relevance
“…Disregarding the CV of the nodulation traits, which were high, the traits determined by counting showed a lower mean, of 25.78% for all cultivars and irrigation conditions, whereas those obtained by measuring averaged 43.61%, suggesting that, for the same level of experimental precision, more samples are needed for the measured traits than for the counted ones. Schoffel et al (2020) observed the same result in cassava in an experiment evaluating vegetative traits.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Disregarding the CV of the nodulation traits, which were high, the traits determined by counting showed a lower mean, of 25.78% for all cultivars and irrigation conditions, whereas those obtained by measuring averaged 43.61%, suggesting that, for the same level of experimental precision, more samples are needed for the measured traits than for the counted ones. Schoffel et al (2020) observed the same result in cassava in an experiment evaluating vegetative traits.…”
Section: Resultssupporting
confidence: 60%
“…This variability in sample size denotes that the results are adequate, as they reflect real experimental situations. The same was found for millet (Kleinpaul et al, 2017), flax (Cargnelutti et al, 2018a), jack bean (Cagnelutti et al, 2018b, rosemary (Schoffel et al, 2019), and cassava (Schoffel et al, 2020).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Los intervalos de confianza determinados por el remuestreo se utilizan para calcular el tamaño de la muestra. Esta técnica es independiente de la distribución de probabilidad de los datos y se ha utilizado para estimar los promedios de rasgos en lupino blanco(Burin et al, 2014).El tamaño de la muestra no siempre se elige de acuerdo con la variabilidad de los datos y el nivel deseado de precisión de la estimación, lo que puede comprometer la calidad del estudio Schoffel et al (2020). determinó el tamaño de la muestra para estimar los promedios de rasgos agronómicos en plántulas de yuca procedentes de esquejes de tallos cortados con un número diferente de hojas y diferentes diámetros.…”
unclassified
“…Assim, amostragens de uma parcela da população que seja representativa do grupo como um todo é uma alternativa para o pesquisador. Para isso, a definição de um tamanho da amostra apropriado durante o planejamento da pesquisa é um ponto crucial para se obter resultados confiáveis (Schoffel et al, 2020).…”
Section: Introdução Geralunclassified